Complete blood count risk score and its components, including RDW, are associated with mortality in the JUPITER trial. (April 2015) - Horne, Benjamin D; Anderson, Jeffrey L; Muhlestein, Joseph B; Ridker, Paul M; Paynter, Nina P
Background: Previously, we showed that sex-specific complete blood count (CBC) risk scores strongly predicted risk of all-cause mortality in multiple sets of general medical patients. This study evaluated the CBC risk score in an independent, well-studied international primary risk population of lower-risk individuals initially free from cardiovascular (CV) disease. Design: Observational secondary analysis of a randomized trial population. Methods: The previously derived and validated CBC score was evaluated for association with all-cause mortality among CV disease-free females ( n = 6568) and males ( n = 10, 629) enrolled for up to 5 years in the Justification for the Use of Statins in Prevention: an Intervention Trial Evaluating Rosuvastatin (JUPITER) trial. Associations of the CBC score with CV mortality and with major CV disease were also tested. Results: The CBC score predicted all-cause mortality, with univariable hazard ratio (HR) 4.83 (95% CI 3.70–6.31) for the third CBC score tertile vs. the first tertile, and HR 2.31 (CI 1.75–3.05) for the second tertile ( p trend < 0.001). The CBC score retained significance after adjustment: HR 1.97 (CI 1.46–2.67) and 1.51 (CI 1.13–2.00) for tertiles 3 and 2 vs. 1, respectively ( p trend < 0.001). The CBC score also predicted CV mortality ( p trend = 0.025) and the primary JUPITER endpoint ( p trend = 0.015). c-statistics for mortality were 0.729 among all, and 0.722 and 0.750 for females and males, respectively. Conclusions: The CBC risk score was strongly associated with all-cause mortality among JUPITER trial participants and had good discrimination. It also predicted CV-specific outcomes. This CBC score may be useful in identifying cardiac disease-free individuals at increased risk of mortality.